Primary capillary hemangioblastoma of peripheral soft tissues - Michal, Michal; Vanecek, Tomas; Sima, Radek; Mukensnabl, Petr; Boudova, Ludmila; Brouckova, Martina; Koudepa, Karep (The American journal of surgical pathology, 2004)
A case of capillary hemangioblastoma located in the peripheral soft tissue of the inner ankle in a 74-year-old woman is presented. The tumor was an unencapsulated but sharply circumscribed nodule 2.5 cm in size, of a yellow-white color. It showed reddish-brown spots with small cysts up to 2 mm filled with blood. Grossly the tumor was not attached to any peripheral nerve. Signs of von Hippel-Lindau's disease were excluded by thorough clinical evaluation. No additional tumor or erythrocytosis was found in the patient clinically. Immunohistochemically, the tumor stromal cell reacted strongly with antibodies to S-100 protein, NSE, and calponin and they were negative with antibodies to GFAP, CD34, CD31, cytokeratins, actin, desmin, EMA, and HMB-45. Endothelium of the capillaries reacted positively with antibodies to CD31, CD34, and Factor VIII-related protein. Capillary pericytes were actin-positive. All cells of the tumor stained positively with antibody to vimentin. MIB1 antibody reacted only in very few cells (<1%). Ultrastructurally, the stromal cells contained electron-lucent cytoplasm with lipid droplets, a small amount of rough endoplasmic reticulum, and glycogen particles. No electron-dense structures typical of secretory granules were seen in the stromal cells. No mutation of coding sequence of VHL gene was found.
Keywords: Calponins; Soft Tissue Neoplasms; Hemangioblastoma; Humans; Endothelium, Vascular; cévní endotel; calponiny; Antigens, CD34; Calcium-Binding Proteins; Female; Aged; mikrofilamentové proteiny; hemangioblastom; senioři; lidé; Immunohistochemistry; Vimentin; antigeny CD34; imunohistochemie; nádory měkkých tkání; Ankle; Platelet Endothelial Cell Adhesion Molecule-1; S100 Proteins; ženské pohlaví; fosfopyruváthydratasa; kotník; Phosphopyruvate Hydratase; proteiny vázající vápník; von Willebrandův faktor; Microfilament Proteins; antigeny CD31; von Willebrand Factor; vimentin; proteiny S100